Tier 3 of the RTI model : problem solving through a case study approach - Hunley, Sawyer A.; McNamara, Kathy; National Association of School Psychologists (Thousand Oaks, CA : Corwin, 2010)
Provides an overview of the third tier of response to intervention (RTI), and offers guidelines on building a case study in order to identify problems, monitor progress, select an intervention, and provide tools and assessments for students who struggle in the classroom.
Introduction to RTI and the case study model -- Assessment principles and practices -- Facilitating response to intervention in schools -- Problem identification -- Problem analysis -- Single case design -- Intervention -- Evaluating case study outcomes -- Using the case study to determine special education eligibility -- Program evaluation -- Appendix A: recording forms (Morgan) -- Appendix B: recording forms (Reggie).
"A joint publication, National Association of School Psychologists.".
Includes bibliographical references (p. 215-224) and index.
Professional
Keywords: Behavior disorders in children -- Treatment -- United States -- Case studies; Problem children -- Education -- United States -- Case studies; Remedial teaching -- United States -- Case studies; School failure -- United States -- Prevention -- Case studies; Emotionally disturbed children -- United States -- Education -- Case studies; Emotionally disturbed children -- United States -- Treatment -- Case studies; Remedial teaching -- Case studies